(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: extradural haematoma; Glasgow Coma Scale; pupillary dilatation; computerized axial tomography doi: 10.3329/jcmcta.v19i1.3843 Journal of Chittagong Medical College Teachers’ Association 2008: 19(1):8-10